Positive electrode active material, preparation method thereof, positive electrode plate containing positive electrode active material, battery and electric device

By generating a coating layer composed of Na, M and O elements on the substrate surface of the positive electrode active material of the sodium battery, the problem of the loss of active sodium and the easy decomposition of sodium supplementary additives during the first charge is solved, and high first discharge is achieved Capacity, high Coulomb efficiency and good cycle performance.

CN119447276AActive Publication Date: 2025-02-14CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202310976871.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-04
Publication Date
2025-02-14
Estimated Expiration
2043-08-04

Smart Images

  • Figure CN119447276A_ABST
    Figure CN119447276A_ABST
Patent Text Reader

Abstract

The invention discloses a positive active material, a preparation method thereof, a positive pole piece containing the positive active material, a battery and an electric device. The positive electrode active material comprises a substrate and a coating layer generated on at least one part of the surface of the substrate; the matrix comprises a sodium-containing layered transition metal oxide; the coating layer comprises a sodium supplementing material, the coating layer comprises Na element, M element and O element, and M represents transition metal; and the coating layer meets the condition that the concentration of the Na element is reduced from the surface, far away from the substrate, of the coating layer to the surface, close to the substrate, of the coating layer. According to the invention, the battery has high first discharge gram capacity, high first coulombic efficiency and good cycle performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to a positive electrode active material, a preparation method thereof, and a positive electrode sheet, a battery and an electrical device containing the same. Background Art

[0002] In recent years, batteries have been widely used in energy storage power systems such as hydropower, thermal power, wind power and solar power stations, as well as power tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, aerospace and other fields. At present, lithium batteries still occupy the core position of batteries, and lithium batteries also face great challenges, such as the increasing shortage of lithium resources. Sodium resources are far more abundant than lithium resources, are more widely distributed, and have a much lower cost than lithium. Therefore, sodium batteries have become a new generation of electrochemical systems with great potential to replace lithium batteries. Similar to lithium batteries, when sodium batteries are charged for the first time, a solid electrolyte interface (SEI) film will be formed on the surface of the negative electrode. This process will irreversibly consume the active sodium of the positive electrode, thereby reducing the battery's first discharge capacity and first coulombic efficiency.

[0003] Sodium supplementation for the positive electrode is one of the effective methods to solve the above problems. At present, the methods for sodium supplementation of the positive electrode mainly include spraying sodium powder method, introducing sodium supplementation additives, etc. The spraying sodium powder method has extremely stringent environmental requirements and is difficult to produce and apply on a large scale. The sodium supplementation method of introducing sodium supplementation additives is to add sodium supplementation additives to the positive electrode slurry to make a positive electrode sheet. The sodium supplementation additive will decompose and provide active sodium within the working range of the sodium battery, thereby compensating for the loss of active sodium and improving the battery's first discharge gram capacity and first coulomb efficiency. However, the sodium supplementation additives currently used have the following problems: the product after sodium supplementation additives are dehydrated is inactive, thereby reducing the energy density of the battery; the sodium supplementation additives are easily decomposed to produce gas, thereby affecting the battery's cycle performance.

[0004] The above statements are only used to provide background information related to the present application and do not necessarily constitute prior art. Summary of the invention

[0005] The present application provides a positive electrode active material, a preparation method thereof, a positive electrode plate, a battery and an electrical device comprising the same, which can enable the battery to have high first discharge gram capacity, high first coulomb efficiency and good cycle performance.

[0006] In a first aspect, the present application provides a positive electrode active material, which includes a substrate and a coating layer generated on at least a portion of the surface of the substrate; the substrate includes a sodium-containing layered transition metal oxide; the coating layer includes a sodium-supplementing material, the coating layer includes Na element, M element and O element, M represents a transition metal; and the coating layer satisfies: the concentration of the Na element tends to decrease from the surface of the coating layer away from the substrate to the surface of the coating layer close to the substrate.

[0007] The positive electrode active material includes a substrate and a coating layer formed on at least a portion of the surface of the substrate, and the coating layer includes a sodium supplement material. When the battery is charged for the first time, the active sodium in the sodium supplement material can make up for the active sodium loss caused by the formation of the SEI film at the negative electrode, thereby improving the first discharge gram capacity and the first coulomb efficiency of the battery. The concentration of the Na element in the coating layer tends to decrease from the surface of the coating layer away from the substrate to the surface of the coating layer close to the substrate, which is conducive to promoting the release of active sodium, thereby facilitating the battery to have a higher first discharge gram capacity and a higher first coulomb efficiency.

[0008] The coating layer includes Na, M and O elements, so that the sodium supplement material in the coating layer has a low risk of decomposing and producing gas, and can make the positive electrode film layer and the positive electrode current collector have good adhesion, thereby making the battery have good cycle performance. In addition, the positive electrode active material provided in the embodiment of the present application can exist stably in the air and has low environmental requirements.

[0009] Therefore, the positive electrode active material provided in the embodiments of the present application can enable the battery to have high first discharge gram capacity, high first coulombic efficiency and good cycle performance.

[0010] In any embodiment, the sodium-containing layered transition metal oxide includes M' element, M' represents a transition metal, and the average valence of the M' element in the sodium-containing layered transition metal oxide is greater than the average valence of the M element in the coating layer. The average valence of the transition metal element in the coating layer is low, so the coating layer has higher stability and lower risk of decomposition and gas generation, which can further improve the adhesion between the positive electrode film layer and the positive electrode current collector, reduce the positive electrode contact resistance, and further improve the cycle performance of the battery.

[0011] In any embodiment, the coating layer satisfies: the average valence of the M element increases from the surface of the coating layer away from the substrate to the surface of the coating layer close to the substrate. This can improve the stability of the coating layer and reduce the risk of decomposition and gas generation of the coating layer, thereby further improving the adhesion between the positive electrode film layer and the positive electrode current collector, reducing the positive electrode contact resistance, and further improving the cycle performance of the battery.

[0012] In any embodiment, in the coating layer, M includes one or more of Ni, Mn, Fe, Co, Cr, Cu, V, and Ti, and may optionally include two or more of Ni, Mn, Fe, Co, Cr, Cu, V, and Ti.

[0013] In any embodiment, in the sodium-containing layered transition metal oxide, M′ includes one or more of Ni, Mn, Fe, Co, Cr, Cu, V, and Ti, and may optionally include two or more of Ni, Mn, Fe, Co, Cr, Cu, V, and Ti.

[0014] In any embodiment, the coating layer is in-situ generated on at least a portion of the surface of the substrate. The coating layer is in-situ generated on at least a portion of the surface of the substrate, so the bonding strength between the coating layer and the substrate is relatively high. After the active sodium in the sodium-supplemented material is extracted, the remaining material (i.e., the remaining product after the sodium-supplemented material is de-sodiumized) can also allow the coating layer to isolate the electrolyte from direct contact with the substrate, thereby reducing the side reactions of the battery, and further helping to improve the cycle performance of the battery. In addition, after the active sodium in the sodium-supplemented material is extracted, the remaining material (i.e., the remaining product after the sodium-supplemented material is de-sodiumized) can be stably present in the coating layer, thereby reducing the probability of transition metal ions in the remaining material (i.e., the remaining product after the sodium-supplemented material is de-sodiumized) dissolving into the electrolyte, and further helping to improve the cycle performance of the battery.

[0015] In any embodiment, the thickness H of the coating layer and the average diameter D of the positive electrode active material satisfy: 0<H / D≤0.15, optionally, 0.02≤H / D≤0.11. This can effectively reduce the side reaction between the electrolyte and the matrix, thereby improving the cycle performance of the battery, and also helping the battery to have a high first discharge gram capacity and a high first coulombic efficiency.

[0016] In any embodiment, the weight content of the coating layer in the positive electrode active material is 2%-40%, optionally 5%-20%, based on the total weight of the positive electrode active material, thereby enabling the battery to have high first discharge gram capacity, high first coulomb efficiency and good cycle performance.

[0017] In any embodiment, the volume distribution particle size Dv50 of the positive electrode active material is 1 μm-10 μm, and can be optionally 3 μm-8 μm. The volume distribution particle size Dv50 of the positive electrode active material within the above range can further improve the ion transport performance and electron transport performance of the positive electrode active material, and can also reduce the side reaction between the electrolyte and the matrix material, thereby facilitating the improvement of the cycle performance and / or rate performance of the battery.

[0018] In any embodiment, in the coating layer, the chemical molar ratio of the Na element, the M element and the O element is (1-6): (1-2): (2-4), and optionally, the chemical molar ratio of the Na element, the M element and the O element is (1-6): 1: (2-4). This can improve the first discharge gram capacity and the first coulombic efficiency of the battery.

[0019] In any embodiment, the coating layer includes one or more of NaMO2, Na2MO2, Na2MO3, Na3MO2, Na3MO3, Na4MO3, Na5MO3, Na5MO4, and Na6MO4, and may include two or more of NaMO2, Na2MO2, Na2MO3, Na3MO2, Na3MO3, Na4MO3, Na5MO3, Na5MO4, and Na6MO4. Optionally, M independently includes any one of Ni, Mn, Fe, Co, Cr, Cu, V, and Ti.

[0020] In any embodiment, the sodium-containing layered transition metal oxide comprises Na c N d M″ e P f O g Q h , 0.67≤c≤1.2, 0≤d≤1 / 3, 0<e≤1, 0≤f≤1 / 3, 1.9≤g≤2, 0≤h≤0.1, and the values ​​of c, d, e, f, g, and h satisfy the charge balance of the chemical formula; M″ includes one or more of Ni, Mn, Fe, Co, Cr, Cu, V, and Ti, and can be selected to include two or more of Ni, Mn, Fe, Co, Cr, Cu, V, and Ti; N includes one or more metal elements of Group IA, Group IIA, and Zn, and can be selected to include one or more elements of Li, Mg, Ca, and Zn; P includes one or more of a first metal element and a first non-metal element, and the first metal element It includes one or more metal elements from Group IA, Group IIA, Group IIIA, Group IVA, Group VA, Group IIB, Group IVB, Group VB, and Group VIB, and can be selected to include one or more elements from the group consisting of Li, Zr, Sb, Nb, Mg, Ca, Mo, Zn, W, Bi, Sn, Ge, Al, Ba, and Sr; the first non-metallic element includes one or more non-metallic elements from Group IIIA, Group IVA, Group VA, and Group VIA, and can be selected to include one or more elements from the group consisting of Si, P, B, S, and Se; Q includes one or more non-metallic elements from Group VA and Group VIIA, and can be selected to include one or more elements from the group consisting of F, Cl, and N.

[0021] In any embodiment, the sodium-containing layered transition metal oxide includes one or more of an O3 phase, a P2 phase, and a P3 phase.

[0022] In any embodiment, the weight content of the sodium supplement material in the coating layer is greater than 97%, and can be optionally 97%-99%, based on the total weight of the coating layer.

[0023] In any embodiment, the coating layer further includes one or more of sodium oxide, sodium hydroxide, and sodium carbonate.

[0024] In any embodiment, the sodium-containing layered transition metal oxide includes M' element and non-valent metal element, M' represents transition metal, and the coating layer also includes one or more of oxide and salt of non-valent metal element.

[0025] The second aspect of the present application provides a method for preparing a positive electrode active material, comprising the following steps: providing a sodium-containing layered transition metal oxide and an aryl sodium solution; mixing the sodium-containing layered transition metal oxide and the aryl sodium solution to react, washing and drying after the reaction to obtain a powder; sintering the obtained powder under an inert gas atmosphere to obtain a positive electrode active material, wherein the positive electrode active material includes a substrate and a coating layer generated on at least a portion of the surface of the substrate; the substrate includes a sodium-containing layered transition metal oxide; the coating layer includes a sodium supplement material, the coating layer includes Na element, M element and O element, M represents a transition metal; and the coating layer satisfies: the concentration of the Na element tends to decrease from the surface of the coating layer away from the substrate to the surface of the coating layer close to the substrate.

[0026] The method for preparing the positive electrode active material provided in the embodiment of the present application has a simple process and is suitable for large-scale production.

[0027] The positive electrode active material prepared by the preparation method provided in the embodiments of the present application can enable the battery to have high first discharge gram capacity, high first coulombic efficiency and good cycle performance.

[0028] In any embodiment, in the step of mixing the sodium-containing layered transition metal oxide with the aryl sodium solution for reaction, the molar ratio of the sodium-containing layered transition metal oxide to the Na element in the aryl sodium is 1:(0.01-0.2), and can be optionally 1:(0.05-0.1). When the molar ratio of the sodium-containing layered transition metal oxide to the Na element in the aryl sodium is within the above range, it is beneficial to in-situ generate a coating layer on the surface of the substrate, and it is also beneficial to obtain a positive electrode active material with high structural stability, thereby facilitating the battery to have both high first discharge gram capacity, high first coulomb efficiency and good cycle performance.

[0029] In any embodiment, in the step of mixing the sodium-containing layered transition metal oxide with the aryl sodium solution for reaction, the reaction temperature is 15°C-60°C, optionally 25°C-45°C. When the reaction temperature is within the above range, it is beneficial to increase the reaction rate, shorten the reaction time, and improve the bonding strength between the coating layer and the substrate, and reduce the probability of the coating layer falling off during sintering. In addition, when the reaction temperature is within the above range, it is also beneficial to reduce sodium loss, and it is also beneficial for the battery to have high first discharge gram capacity, high first coulomb efficiency and good cycle performance.

[0030] In any embodiment, in the step of mixing the sodium-containing layered transition metal oxide with the aryl sodium solution for reaction, the reaction time is 5h-20h, and can be optionally 8h-16h. When the reaction time is within the above range, it is beneficial to increase the reaction rate, shorten the reaction time, and also to increase the bonding strength between the coating layer and the substrate, and reduce the probability of the coating layer falling off during sintering. In addition, when the reaction time is within the above range, it is also beneficial to reduce sodium loss, and it is also beneficial for the battery to have high first discharge gram capacity, high first coulomb efficiency and good cycle performance.

[0031] In any embodiment, in the step of mixing the sodium-containing layered transition metal oxide with the sodium aryl solution for reaction, the reaction is carried out under stirring conditions. Optionally, the stirring speed is 100 r / min-1000 r / min, and more preferably 200 r / min-700 r / min.

[0032] In any embodiment, in the step of sintering the obtained powder under an inert gas atmosphere, the sintering temperature is 500° C.-950° C., and can be 600° C.-900° C. When the sintering temperature is within the above range, it is beneficial for the reduced transition metal element and / or low-valent transition metal oxide to react with Na2O to generate sodium supplement material, and it is also beneficial to improve the bonding strength between the coating layer and the substrate, thereby facilitating the battery to have high first discharge gram capacity, high first coulomb efficiency and good cycle performance.

[0033] In any embodiment, in the step of sintering the obtained powder under an inert gas atmosphere, the holding time of the sintering treatment is 3h-9h, and can be optionally 5h-8h. When the holding time of the sintering treatment is within the above range, it is beneficial for the reduced transition metal element and / or low-valent transition metal oxide to react with Na2O to generate sodium supplement material, and it is also beneficial to improve the bonding strength between the coating layer and the substrate, thereby facilitating the battery to have high first discharge gram capacity, high first coulomb efficiency and good cycle performance.

[0034] In any embodiment, in the step of sintering the obtained powder under an inert gas atmosphere, the inert gas includes one or more of argon, helium, nitrogen, and a hydrogen-argon mixed gas.

[0035] In any embodiment, the concentration of the sodium aryl solution is 0.5 mol / L-3.5 mol / L, and can be 1 mol / L-2 mol / L. When the concentration of the sodium aryl solution is within the above range, it is beneficial for the battery to have high first discharge gram capacity, high first coulombic efficiency and good cycle performance.

[0036] In any embodiment, the aryl sodium includes one or more of sodium naphthalene, sodium biphenyl, sodium phenyl, sodium phenanthrene, sodium anthracene, sodium pyrene, sodium bipyridine, and sodium tetracene. These aryl sodiums have a large electronegativity, which is conducive to reducing the transition metal in the surface layer of the sodium-containing layered transition metal oxide.

[0037] In any embodiment, the solvent of the sodium aryl solution includes an aprotic solvent. Therefore, when the sodium-containing layered transition metal oxide reacts with the sodium aryl solution, the release of sodium between the layers of the sodium-containing layered transition metal oxide can be reduced, thereby facilitating the battery to have good cycle performance.

[0038] Optionally, the aprotic solvent includes one or more of ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, tetrahydrofuran, N,N-dimethylformamide, diethyl ether, diisopropyl ether, diethylene glycol dimethyl ether, methyl tert-butyl ether, ether, acetonitrile, and dimethyl sulfoxide. When the aprotic solvent is within the above range, the release of sodium between the sodium-containing layered transition metal oxide layers can be reduced, which is conducive to the battery having good cycle performance.

[0039] In any embodiment, the sodium-containing layered transition metal oxide comprises Na c N d M″ e P f O g Q h, 0.67≤c≤1.2, 0≤d≤1 / 3, 0<e≤1, 0≤f≤1 / 3, 1.9≤g≤2, 0≤h≤0.1, and the values ​​of c, d, e, f, g, and h satisfy the charge balance of the chemical formula; M″ includes one or more of Ni, Mn, Fe, Co, Cr, Cu, V, and Ti, and can be selected to include two or more of Ni, Mn, Fe, Co, Cr, Cu, V, and Ti; N includes one or more metal elements of Group IA, Group IIA, and Zn, and can be selected to include one or more elements of Li, Mg, Ca, and Zn; P includes one or more of a first metal element and a first non-metal element, and the first metal element It includes one or more metal elements from Group IA, Group IIA, Group IIIA, Group IVA, Group VA, Group IIB, Group IVB, Group VB, and Group VIB, and can be selected to include one or more elements from the group consisting of Li, Zr, Sb, Nb, Mg, Ca, Mo, Zn, W, Bi, Sn, Ge, Al, Ba, and Sr; the first non-metallic element includes one or more non-metallic elements from Group IIIA, Group IVA, Group VA, and Group VIA, and can be selected to include one or more elements from the group consisting of Si, P, B, S, and Se; Q includes one or more non-metallic elements from Group VA and Group VIIA, and can be selected to include one or more elements from the group consisting of F, Cl, and N.

[0040] The third aspect of the present application provides a positive electrode plate, which includes a positive electrode collector and a positive electrode film layer arranged on at least one surface of the positive electrode collector, and the positive electrode film layer includes the positive electrode active material of the first aspect of the present application or the positive electrode active material prepared by the preparation method of the second aspect of the present application.

[0041] In any embodiment, the weight content of the positive electrode active material in the positive electrode film layer is 50%-99%, optionally 80%-99%, based on the total weight of the positive electrode film layer.

[0042] A fourth aspect of the present application provides a battery, which includes the positive electrode plate of the third aspect of the present application.

[0043] A fifth aspect of the present application provides an electrical device, which includes the battery of the fourth aspect of the present application, and the battery is used to provide electrical energy.

[0044] The electric device of the present application includes the battery provided by the present application, and thus has at least the same advantages as the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the following briefly introduces the drawings required for use in the embodiments of the present application. Obviously, the drawings described below are only some implementation methods of the present application, and for ordinary technicians in this field, other drawings can be obtained based on the drawings without creative work.

[0046] Figure 1 It is a schematic diagram of an embodiment of a battery cell of the present application.

[0047] Figure 2 yes Figure 1 An exploded schematic diagram of an embodiment of a battery cell.

[0048] Figure 3 It is a schematic diagram of an embodiment of a battery module of the present application.

[0049] Figure 4 It is a schematic diagram of an embodiment of the battery pack of the present application.

[0050] Figure 5 yes Figure 4 An exploded schematic diagram of an embodiment of a battery pack is shown.

[0051] Figure 6 It is a schematic diagram of an embodiment of an electrical device including the battery of the present application as a power source.

[0052] In the drawings, the drawings may not be drawn according to the actual scale. The reference numerals are as follows: 1 battery pack, 2 upper box, 3 lower box, 4 battery module, 5 battery cell, 51 housing, 52 electrode assembly, 53 cover plate. DETAILED DESCRIPTION

[0053] Hereinafter, the embodiments of the positive electrode active material, the preparation method thereof, and the positive electrode sheet, battery, and electrical device containing the same will be specifically disclosed with appropriate reference to the drawings. However, there will be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structures are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.

[0054] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values ​​or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0055] If not otherwise specified, all embodiments and optional embodiments of the present application may be combined with each other to form new technical solutions, and such technical solutions should be deemed to be included in the disclosure of the present application.

[0056] Unless otherwise specified, all technical features and optional technical features of the present application may be combined with each other to form new technical solutions, and such technical solutions should be deemed to be included in the disclosure of the present application.

[0057] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may also include step (c), indicating that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0058] In the present application, the terms "plurality" and "multiple" refer to two or more.

[0059] Unless otherwise specified, the terms used in this application have the commonly understood meanings that are commonly understood by those skilled in the art.

[0060] Unless otherwise specified, the values ​​of the parameters mentioned in this application can be measured by various test methods commonly used in the art, for example, they can be measured according to the test methods given in the examples of this application. Unless otherwise specified, the test temperature of each parameter is 25°C.

[0061] The battery mentioned in the embodiments of the present application may be a single physical module including one or more battery cells to provide higher voltage and capacity. For example, the battery mentioned in the present application may include a battery cell, a battery module or a battery pack.

[0062] A battery cell is the smallest unit of a battery, which can independently realize the functions of charging and discharging. The battery cell can be cylindrical, rectangular or in other shapes, etc., which is not limited in the embodiments of the present application. Figure 1 The battery cell 5 is a rectangular parallelepiped structure as an example.

[0063] When there are multiple battery cells, the multiple battery cells are connected in series, in parallel, or in mixed connection through a busbar. In some embodiments, the battery may be a battery module; when there are multiple battery cells, the multiple battery cells are arranged and fixed to form a battery module. In some embodiments, the battery may be a battery pack, which includes a case and battery cells, and the battery cells or battery modules are accommodated in the case. In some embodiments, the case may serve as part of the chassis structure of the vehicle. For example, part of the case may become at least a part of the floor of the vehicle, or part of the case may become at least a part of the crossbeam and longitudinal beam of the vehicle.

[0064] In some embodiments, the battery may be an energy storage device, which includes an energy storage container, an energy storage cabinet, and the like.

[0065] A battery cell generally includes an electrode assembly and an electrolyte. The electrode assembly generally includes a positive electrode sheet and a negative electrode sheet. The electrode assembly may be a wound structure or a laminated structure, which is not limited in the present application.

[0066] The battery cell may also include an outer package, which may be used to encapsulate the electrode assembly and the electrolyte. The outer package may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer package may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, such as one or more of polypropylene (PP), polybutylene terephthalate (PBT) and polybutylene succinate (PBS).

[0067] In some embodiments, Figure 2As shown, the outer package may include a shell 51 and a cover plate 53. The shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 is used to cover the opening to close the receiving cavity. The electrode assembly 52 is encapsulated in the receiving cavity. The number of electrode assemblies 52 contained in the battery cell 5 can be one or more, which can be adjusted according to demand.

[0068] In some embodiments, battery cells may be assembled into a battery module. The battery module may contain multiple battery cells, and the specific number may be adjusted according to the application and capacity of the battery module. Figure 3 FIG. 4 is a schematic diagram of a battery module 4 as an example. Figure 3 As shown, in the battery module 4, the plurality of battery cells 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. Further, the plurality of battery cells 5 may be fixed by fasteners.

[0069] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of battery cells 5 are received in the receiving space.

[0070] In some embodiments, the battery modules described above may also be assembled into a battery pack, and the number of battery modules contained in the battery pack may be adjusted according to the application and capacity of the battery pack.

[0071] Figure 4 and Figure 5 FIG. 1 is a schematic diagram of a battery pack 1 as an example. Figure 4 and Figure 5 As shown, the battery pack 1 may include a box body and a plurality of battery modules 4 disposed in the box body. The box body includes an upper box body 2 and a lower box body 3, and the upper box body 2 is used to cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 may be arranged in the box body in any manner.

[0072] The battery provided in the embodiments of the present application is a sodium battery, which may include, for example, a sodium ion battery, a sodium metal battery, a negative electrode-free sodium metal battery, etc., but the embodiments of the present application are not limited to this.

[0073] A negative electrode-free sodium metal battery generally refers to a battery that is formed by not actively setting a negative electrode active material layer on the negative electrode side during the manufacturing process of the battery, for example, a sodium metal layer is not set at the negative electrode through processes such as coating or deposition, or a negative electrode active material layer is formed by a carbonaceous active material layer during the manufacturing process of the battery. During the first charge, the sodium ions obtain electrons on the negative electrode side and deposit on the surface of the negative electrode current collector to form metallic sodium. During discharge, the metallic sodium can be converted into sodium ions and return to the positive electrode to achieve cyclic charge and discharge. Compared with other batteries, a negative electrode-free sodium metal battery can obtain a higher energy density because it has no negative electrode active material layer. In some embodiments, in order to improve battery performance, some conventional substances that can be used as negative electrode active materials, such as carbon materials, can also be set on the negative electrode side of the negative electrode-free sodium metal battery. Although these substances have a certain capacity, due to their low content and not being used as the main negative electrode active material in the battery, the battery thus constructed can still be regarded as a negative electrode-free sodium metal battery. The CB (Cell Balance) value of the negative electrode-free sodium metal battery is usually very small. For example, in some embodiments, the CB value of the negative electrode-free sodium metal battery can be less than or equal to 0.1. The CB value is the unit area capacity of the negative electrode in the battery divided by the unit area capacity of the positive electrode. Since the negative electrode-free sodium metal battery does not contain or contains only a small amount of negative electrode active material, the unit area capacity of the negative electrode is small, and thus the CB value is very small, for example, usually less than or equal to 0.1.

[0074] The sodium supplement additives currently used in the positive electrode of the battery have the following problems: after the active sodium in some sodium supplement additives is released, a by-product with a relatively high mass ratio will be left in the positive electrode film layer. The by-product has no reaction activity, thereby reducing the energy density of the battery. At the same time, the transition metal ions in the by-products are also easily dissolved into the electrolyte. Subsequently, these transition metal ions will be reduced and deposited on the negative electrode, thereby destroying the structure of the SEI film, reducing the capacity of the battery and affecting the release and embedding of sodium ions; some organic additives (such as sodium oxalate, etc.) and inorganic additives (such as sodium carbonate, sodium nitride, sodium peroxide, etc.) are also easy to decompose and produce gas, thereby leaving more holes in the positive electrode film layer, thereby reducing the adhesion between the positive electrode film layer and the positive electrode current collector, increasing the contact resistance of the positive electrode, and thus affecting the electrochemical performance of the battery.

[0075] In view of this, the embodiments of the present application propose a novel positive electrode active material, which can be used in a sodium battery and enables the sodium battery to have a high first discharge gram capacity, a high first coulombic efficiency and good cycle performance.

[0076] The positive electrode active material provided in the embodiment of the present application includes a substrate and a coating layer formed on at least a portion of the surface of the substrate, the substrate includes a layered transition metal oxide containing sodium, and the coating layer includes a sodium supplement material. The coating layer includes Na element, M element and O element, and M represents a transition metal. And the coating layer satisfies: the concentration of the Na element tends to decrease from the surface of the coating layer away from the substrate to the surface of the coating layer close to the substrate.

[0077] The positive electrode active material includes a substrate and a coating layer formed on at least a portion of the surface of the substrate, and the coating layer includes a sodium supplement material. When the battery is charged for the first time, the active sodium in the sodium supplement material can make up for the active sodium loss caused by the formation of the SEI film at the negative electrode, thereby improving the first discharge gram capacity and the first coulomb efficiency of the battery. The concentration of the Na element in the coating layer tends to decrease from the surface of the coating layer away from the substrate to the surface of the coating layer close to the substrate, which is conducive to promoting the release of active sodium, thereby facilitating the battery to have a higher first discharge gram capacity and a higher first coulomb efficiency.

[0078] The coating layer includes Na, M and O elements, so that the sodium supplement material in the coating layer has a low risk of decomposing and producing gas, and can make the positive electrode film layer and the positive electrode current collector have good adhesion, thereby making the battery have good cycle performance. In addition, the positive electrode active material provided in the embodiment of the present application can exist stably in the air and has low environmental requirements.

[0079] Therefore, the positive electrode active material provided in the embodiments of the present application can enable the battery to have high first discharge gram capacity, high first coulombic efficiency and good cycle performance.

[0080] The concentration of Na element at different positions of the coating layer can be tested using electron probe microanalysis (EPMA), inductively coupled plasma atomic emission spectroscopy (ICP-AES), time-of-flight secondary ion mass spectrometry (ToF-SIMS), EDAX-SEM analysis, X-ray photoelectron spectroscopy (XPS), energy dispersive spectrometer (EDS) and other methods.

[0081] In some embodiments, the coating layer is in-situ generated on at least a portion of the surface of the substrate. The coating layer is in-situ generated on at least a portion of the surface of the substrate, so the bonding strength between the coating layer and the substrate is relatively high. After the active sodium in the sodium-supplemented material is extracted, the remaining material (i.e., the remaining product after the sodium-supplemented material is de-sodiumized) can also allow the coating layer to isolate the electrolyte from direct contact with the substrate, thereby reducing the side reactions of the battery, and further helping to improve the cycle performance of the battery. In addition, after the active sodium in the sodium-supplemented material is extracted, the remaining material (i.e., the remaining product after the sodium-supplemented material is de-sodiumized) can be stably present in the coating layer, thereby reducing the probability of transition metal ions in the remaining material (i.e., the remaining product after the sodium-supplemented material is de-sodiumized) dissolving into the electrolyte, and further helping to improve the cycle performance of the battery.

[0082] In some embodiments, the sodium-containing layered transition metal oxide includes an M' element, where M' represents a transition metal, and the average valence of the M' element in the sodium-containing layered transition metal oxide may be greater than the average valence of the M element in the coating layer. The average valence of the transition metal element in the coating layer is low, so the coating layer has higher stability and lower risk of decomposition and gas generation, which can further improve the adhesion between the positive electrode film layer and the positive electrode current collector, reduce the positive electrode contact resistance, and further improve the cycle performance of the battery.

[0083] In some embodiments, the coating layer satisfies: the average valence of the M element increases from the surface of the coating layer away from the substrate to the surface of the coating layer close to the substrate. This can improve the stability of the coating layer and reduce the risk of decomposition and gas generation of the coating layer, thereby further improving the adhesion between the positive electrode film layer and the positive electrode current collector, reducing the positive electrode contact resistance, and further improving the cycle performance of the battery.

[0084] The average valence of the transition metal element M' in the sodium-containing layered transition metal oxide and the average valence of the transition metal element M in the coating layer can be tested by X-ray photoelectron spectroscopy (XPS). During the test, high-purity argon gas can be used as an etching gas to etch the positive electrode active material sample. By controlling the light energy, etching time and other conditions, the average valence of the transition metal element M in the coating layer and the average valence of the transition metal element M' in the sodium-containing layered transition metal oxide matrix can be measured at different positions of the positive electrode active material. The testing instrument can be an escalab 250Xi X-ray photoelectron spectrometer from Thermo Fisher Scientific, USA.

[0085] In some embodiments, the thickness H of the coating layer and the average diameter D of the positive electrode active material satisfy: 0<H / D≤0.15, optionally, 0.02≤H / D≤0.11. This can effectively reduce the side reaction between the electrolyte and the matrix, thereby facilitating the improvement of the cycle performance of the battery, and also facilitating the battery to have a high first discharge gram capacity and a high first coulombic efficiency.

[0086] The thickness H of the coating layer can be measured by methods known in the art. As an example, a cross-section polisher (e.g., IB-09010CP argon ion cross-section polisher from JEOL, Japan) can be used to prepare a cross section of the positive electrode active material particle, which passes through the core of the positive electrode active material particle; then, an energy dispersive spectrometer (EDS) elemental analysis combined with a transmission electron microscope (TEM) or a scanning electron microscope (SEM) surface scanning test is performed to obtain an element distribution diagram in the cross section; the thickness of the coating layer is obtained based on the element distribution of the cross section. During the test, the thickness values ​​of the coating layer at multiple (e.g., more than 10) different positions on the cross section can be counted, and the average value is recorded as the thickness of the coating layer.

[0087] The average diameter D of the positive electrode active material is the average value of the diameters of multiple positive electrode active material particles. For example, the diameters of the positive electrode active material particles at multiple (e.g., more than 10) different positions on the cross section can be obtained based on the element distribution diagram of the positive electrode active material particle cross section obtained above, and the average value is recorded as the average diameter D of the positive electrode active material.

[0088] In some embodiments, the volume distribution particle size Dv50 of the positive electrode active material may be 1 μm-10 μm, and may be 3 μm-8 μm. The volume distribution particle size Dv50 of the positive electrode active material within the above range can further improve the ion transport performance and electron transport performance of the positive electrode active material, and can also reduce the side reaction between the electrolyte and the matrix material, thereby facilitating the improvement of the cycle performance and / or rate performance of the battery.

[0089] The volume distribution particle size Dv50 of the positive electrode active material is well known in the art, which indicates the particle size corresponding to when the cumulative volume distribution percentage of the material reaches 50%, and can be measured by instruments and methods well known in the art. For example, it can be conveniently measured using a laser particle size analyzer with reference to GB / T 19077-2016. The test instrument can be a Mastersizer 2000E laser particle size analyzer from Malvern Instruments Ltd., UK.

[0090] In some embodiments, the weight content of the coating layer in the positive electrode active material may be 2%-40%, optionally 5%-20%, based on the total weight of the positive electrode active material, thereby enabling the battery to have high first discharge gram capacity, high first coulombic efficiency and good cycle performance.

[0091] In some embodiments, in the sodium-containing layered transition metal oxide, M′ may include one or more of Ni, Mn, Fe, Co, Cr, Cu, V, and Ti, and may optionally include two or more of Ni, Mn, Fe, Co, Cr, Cu, V, and Ti.

[0092] In some embodiments, the sodium-containing layered transition metal oxide comprises Na c N d M″ e P f O g Q h , 0.67≤c≤1.2, 0≤d≤1 / 3, 0<e≤1, 0≤f≤1 / 3, 1.9≤g≤2, 0≤h≤0.1, and the values ​​of c, d, e, f, g, and h satisfy the charge balance of the chemical formula; M″ includes one or more of Ni, Mn, Fe, Co, Cr, Cu, V, and Ti; N includes one or more metal elements in Group IA, Group IIA, and Zn; P includes one or more of a first metal element and a first non-metal element, the first metal element includes one or more metal elements in Group IA, Group IIA, Group IIIA, Group IVA, Group VA, Group IIB, Group IVB, Group VB, and Group VIB, and the first non-metal element includes one or more non-metal elements in Group IIIA, Group IVA, Group VA, and Group VIA; Q includes one or more non-metal elements in Group VA and Group VIIA.

[0093] Optionally, M″ may include two or more of Ni, Mn, Fe, Co, Cr, Cu, V, and Ti.

[0094] Optionally, N may include one or more elements of Li, Mg, Ca, and Zn.

[0095] Optionally, the first metal element may include one or more elements of Li, Zr, Sb, Nb, Mg, Ca, Mo, Zn, W, Bi, Sn, Ge, Al, Ba, and Sr.

[0096] Optionally, the first non-metal element may include one or more elements of Si, P, B, S, and Se.

[0097] Optionally, Q may include one or more elements of F, Cl, and N.

[0098] The content of each element in the matrix and coating layer of the positive electrode active material can be detected by inductively coupled plasma emission spectroscopy (ICP) with reference to EPA 6010D-2014. For example, a cross-section polisher (such as the IB-09010CP argon ion cross-section polisher of JEOL, Japan) can be used to prepare the cross section of the positive electrode active material particles; then, with reference to JY / T010-1996, a scanning electron microscope (SEM) or a transmission electron microscope (TEM) is used to scan the cross section of the positive electrode active material particles, and inductively coupled plasma emission spectroscopy (ICP) is used for detection.

[0099] In some embodiments, the sodium-containing layered transition metal oxide may include, but is not limited to, one or more of an O3 phase, a P2 phase, and a P3 phase.

[0100] In some embodiments, in the coating layer, M may include one or more of Ni, Mn, Fe, Co, Cr, Cu, V, and Ti, and may optionally include two or more of Ni, Mn, Fe, Co, Cr, Cu, V, and Ti.

[0101] In some embodiments, in the coating layer, the chemical molar ratio of the Na element, the M element and the O element can be (1-6): (1-2): (2-4), and optionally, the chemical molar ratio of the Na element, the M element and the O element can be (1-6): 1: (2-4). This can improve the first discharge gram capacity and the first coulombic efficiency of the battery.

[0102] In some embodiments, the coating layer may include one or more of NaMO2, Na2MO2, Na2MO3, Na3MO2, Na3MO3, Na4MO3, Na5MO3, Na5MO4, and Na6MO4, and optionally, M independently includes any one of Ni, Mn, Fe, Co, Cr, Cu, V, and Ti. Alternatively, the coating layer may include two or more of NaMO2, Na2MO2, Na2MO3, Na3MO2, Na3MO3, Na4MO3, Na5MO3, Na5MO4, and Na6MO4.

[0103] In some embodiments, the weight content of the sodium supplement material in the coating layer may be greater than 97%, optionally 97%-99%, based on the total weight of the coating layer.

[0104] In some embodiments, the coating layer may further include one or more of sodium oxide, sodium hydroxide, and sodium carbonate.

[0105] In some embodiments, the sodium-containing layered transition metal oxide may include an M′ element and a non-valent metal element, where M′ represents a transition metal, and the coating layer further includes one or more of an oxide of the non-valent metal element and a salt of the non-valent metal element.

[0106] In some embodiments, the morphology of the positive electrode active material may include, but is not limited to, one or more of spherical single crystals, flaky single crystals, and spherical polycrystals.

[0107] The term "single crystal" also includes quasi-single crystals, which means particles composed of several or more than a dozen primary particles. The term "spherical" also includes quasi-spherical shapes, which means that the shape is basically spherical or the aspect ratio is close to 1, for example, the aspect ratio is not greater than 1.3, and optionally not greater than 1.2.

[0108] The morphology of the positive electrode active material can be tested using a scanning electron microscope (SEM), for example, the test can be performed with reference to JY / T010-1996. The testing instrument can be a Sigma 300 scanning electron microscope from the German ZEISS company.

[0109] [Preparation method]

[0110] The present application also provides a method for preparing a positive electrode active material.

[0111] The method comprises the following steps: providing a sodium-containing layered transition metal oxide and an aryl sodium solution; mixing the sodium-containing layered transition metal oxide and the aryl sodium solution to react, washing and drying after the reaction to obtain a powder; sintering the obtained powder under an inert gas atmosphere to obtain a positive electrode active material. The positive electrode active material comprises a substrate and a coating layer formed on at least a portion of the surface of the substrate; the substrate comprises a sodium-containing layered transition metal oxide; the coating layer comprises a sodium supplement material, the coating layer comprises Na element, M element and O element, M represents a transition metal; and the coating layer satisfies: the concentration of the Na element decreases from the surface of the coating layer away from the substrate to the surface of the coating layer close to the substrate.

[0112] The coating layer of the positive electrode active material is obtained by mixing and reacting a sodium-containing layered transition metal oxide with an aryl sodium solution and then sintering. Aryl sodium has reducibility, so after the sodium-containing layered transition metal oxide reacts with the aryl sodium solution, the aryl sodium can reduce the transition metal in the surface layer of the sodium-containing layered transition metal oxide, and after washing and drying, Na2O, transition metal single substance and / or low-valent transition metal oxide can be formed on the surface layer of the sodium-containing layered transition metal oxide. When sintering is performed later, Na2O reacts with transition metal single substance and / or low-valent transition metal oxide to generate sodium supplement material. Therefore, in-situ sodium supplementation can be achieved by mixing and reacting a sodium-containing layered transition metal oxide with an aryl sodium solution and sintering treatment.

[0113] The method for preparing the positive electrode active material provided in the embodiment of the present application has a simple process and is suitable for large-scale production.

[0114] The positive electrode active material prepared by the preparation method provided in the embodiment of the present application can exist stably in the air and has low requirements on the environment.

[0115] When the positive electrode active material prepared by the preparation method provided in the embodiment of the present application is charged for the first time, the active sodium in the sodium supplement material can make up for the active sodium loss caused by the formation of SEI film at the negative electrode, thereby improving the first discharge gram capacity and the first coulombic efficiency of the battery.

[0116] The positive electrode active material prepared by the preparation method provided in the embodiments of the present application can make the concentration of the Na element in the coating layer decrease from the surface of the coating layer far from the substrate to the surface of the coating layer close to the substrate, which is beneficial to promote the release of active sodium, and thus is also beneficial for the battery to have a higher first discharge gram capacity and a higher first coulombic efficiency.

[0117] The positive electrode active material prepared by the preparation method provided in the embodiment of the present application has a low risk of decomposition and gas production during the battery charging and discharging process, thereby enabling good adhesion between the positive electrode film layer and the positive electrode current collector, reducing the positive electrode contact resistance, and thus enabling the battery to have good cycle performance.

[0118] Therefore, the positive electrode active material prepared by the preparation method provided in the embodiment of the present application can enable the battery to have high first discharge gram capacity, high first coulombic efficiency and good cycle performance.

[0119] The coating layer of the positive electrode active material prepared by the preparation method provided in the embodiment of the present application is in-situ generated on at least a portion of the surface of the substrate, so the bonding strength between the coating layer and the substrate is relatively high. After the active sodium in the sodium supplement material is removed, the remaining material (i.e., the remaining product after the sodium supplement material is de-sodiumized) can also make the coating layer isolate the electrolyte from direct contact with the substrate, thereby reducing the side reactions of the battery, and thus helping to further improve the cycle performance of the battery. In addition, after the active sodium in the sodium supplement material is removed, the remaining material (i.e., the remaining product after the sodium supplement material is de-sodiumized) can be stably present in the coating layer, thereby reducing the probability of transition metal ions in the remaining material (i.e., the remaining product after the sodium supplement material is de-sodiumized) dissolving into the electrolyte, thereby helping to further improve the cycle performance of the battery.

[0120] The sodium-containing layered transition metal oxide includes the M' element, where M' represents a transition metal. The positive electrode active material prepared by the preparation method provided in the embodiment of the present application can make the average valence of the M' element in the sodium-containing layered transition metal oxide greater than the average valence of the M element in the coating layer. The average valence of the transition metal element in the coating layer is low, so the coating layer has higher stability and lower risk of decomposition and gas production, which can further improve the adhesion between the positive electrode film layer and the positive electrode current collector, reduce the positive electrode contact resistance, and further improve the cycle performance of the battery.

[0121] The coating layer of the positive electrode active material prepared by the preparation method provided in the embodiment of the present application satisfies: the average valence of the M element increases from the surface of the coating layer far from the substrate to the surface of the coating layer close to the substrate. This can improve the stability of the coating layer and reduce the risk of decomposition and gas generation of the coating layer, thereby further improving the adhesion between the positive electrode film layer and the positive electrode current collector, reducing the positive electrode contact resistance, and further improving the cycle performance of the battery.

[0122] In some embodiments, the solute aryl sodium in the aryl sodium solution may include one or more of sodium naphthalene, sodium biphenyl, sodium phenyl, sodium phenanthrene, sodium anthracene, sodium pyrene, sodium bipyridine, and sodium tetracene. These aryl sodiums have a large electronegativity, which is conducive to reducing the transition metal in the surface layer of the sodium-containing layered transition metal oxide.

[0123] In some embodiments, the solvent of the sodium aryl solution includes an aprotic solvent. Thus, when the sodium-containing layered transition metal oxide reacts with the sodium aryl solution, the release of sodium between the layers of the sodium-containing layered transition metal oxide can be reduced, thereby facilitating the battery to have good cycle performance.

[0124] In some embodiments, the aprotic solvent may include, but is not limited to, one or more of ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, tetrahydrofuran, N,N-dimethylformamide, diethyl ether, diisopropyl ether, diethylene glycol dimethyl ether, methyl tert-butyl ether, ether, acetonitrile, and dimethyl sulfoxide. When the aprotic solvent is within the above range, the sodium release between the sodium-containing layered transition metal oxide layers can be reduced, which is beneficial for the battery to have good cycle performance.

[0125] In some embodiments, the concentration of the aryl sodium solution can be 0.5mol / L-3.5mol / L, for example, it can be 0.5mol / L, 0.8mol / L, 1mol / L, 1.1mol / L, 1.2mol / L, 1.3mol / L, 1.4mol / L, 1.5mol / L, 1.6mol / L, 1.7mol / L, 1.8mol / L, 1.9mol / L, 2mol / L, 2.2mol / L, 2.4mol / L, 2.6mol / L, 2.8mol / L, 3mol / L, 3.5mol / L, or a range consisting of any of the above numerical values.

[0126] When the concentration of the sodium aryl solution is within the above range, it is beneficial to generate a coating layer in situ on the surface of the substrate, and it is also beneficial to reduce the residual alkali content on the surface of the prepared positive electrode active material. The residual alkali mainly includes sodium hydroxide and sodium carbonate. The residual alkali easily causes the positive electrode slurry to gel or solidify, affecting the coating of the positive electrode slurry; the sodium carbonate in the residual alkali has poor thermal stability and is easy to decompose and produce gas under high pressure; the residual alkali does not have electrochemical activity, and when the content increases, it will hinder the transmission of sodium ions. Therefore, when the concentration of the sodium aryl solution is within the above range, it is beneficial for the battery to have high first discharge gram capacity, high first coulomb efficiency and good cycle performance.

[0127] Optionally, the concentration of the aryl sodium solution may be 1 mol / L-2 mol / L.

[0128] The sodium aryl solution can be prepared by methods known in the art, and the present application embodiment does not limit this. For example, sodium metal and an aromatic compound can be reacted in an aprotic solvent to generate highly active sodium aryl to obtain the sodium aryl solution.

[0129] In some embodiments, in the step of mixing the sodium-containing layered transition metal oxide with the aryl sodium solution for reaction, the molar ratio of the sodium-containing layered transition metal oxide to the Na element in the aryl sodium can be 1:(0.01-0.2), and can be optionally 1:(0.05-0.1).

[0130] When the molar ratio of the sodium-containing layered transition metal oxide to the Na element in the aryl sodium is within the above range, it is beneficial to the in-situ generation of a coating layer on the surface of the substrate, and is also beneficial to obtaining a positive electrode active material with high structural stability, thereby helping the battery to have a high first discharge gram capacity, a high first coulombic efficiency and good cycle performance.

[0131] In some embodiments, in the step of mixing the sodium-containing layered transition metal oxide with the sodium aryl solution for reaction, the reaction may be carried out under stirring conditions. This is beneficial to increase the reaction rate and shorten the reaction time. Optionally, the stirring speed may be 100 r / min-1000 r / min, and more preferably 200 r / min-700 r / min.

[0132] In some embodiments, in the step of mixing the sodium-containing layered transition metal oxide with the aryl sodium solution for reaction, the reaction temperature can be 15°C-60°C, for example, 15°C, 20°C, 25°C, 30°C, 35°C, 40°C, 45°C, 50°C, 55°C, 60°C, or a range consisting of any of the above numerical values.

[0133] When the reaction temperature is within the above range, it is beneficial to increase the reaction rate, shorten the reaction time, and improve the bonding strength between the coating layer and the substrate, and reduce the probability of the coating layer falling off during sintering. In addition, when the reaction temperature is within the above range, it is also beneficial to reduce sodium loss, and it is also beneficial for the battery to have high first discharge gram capacity, high first coulomb efficiency and good cycle performance.

[0134] Alternatively, the reaction temperature may be 25°C-45°C.

[0135] In some embodiments, in the step of mixing the sodium-containing layered transition metal oxide with the aryl sodium solution for reaction, the reaction time can be 5h-20h, for example, 5h, 6h, 7h, 8h, 10h, 12h, 14h, 16h, 18h, 20h, or a range consisting of any of the above numerical values.

[0136] When the reaction time is within the above range, it is beneficial to increase the reaction rate, shorten the reaction time, and improve the bonding strength between the coating layer and the substrate, and reduce the probability of the coating layer falling off during sintering. In addition, when the reaction time is within the above range, it is also beneficial to reduce sodium loss, and it is also beneficial for the battery to have high first discharge gram capacity, high first coulomb efficiency and good cycle performance.

[0137] Optionally, the reaction time can be 8h-16h.

[0138] In some embodiments, in the step of sintering the obtained powder under an inert gas atmosphere, the sintering temperature can be 500°C-950°C, for example, 500°C, 550°C, 600°C, 650°C, 700°C, 750°C, 800°C, 850°C, 900°C, 950°C, or a range consisting of any of the above numerical values.

[0139] When the sintering temperature is within the above range, it is beneficial for the reduced transition metal element and / or low-valent transition metal oxide to react with Na2O to generate sodium supplement material, and it is also beneficial to improve the bonding strength between the coating layer and the substrate, which is beneficial for the battery to have high first discharge gram capacity, high first coulomb efficiency and good cycle performance.

[0140] Optionally, the temperature of the sintering process may be 600°C-900°C.

[0141] In some embodiments, in the step of sintering the obtained powder under an inert gas atmosphere, the holding time of the sintering treatment can be 3h-9h, for example, 3h, 4h, 5h, 6h, 7h, 8h, 9h, or a range consisting of any of the above numerical values.

[0142] When the holding time of the sintering treatment is within the above range, it is beneficial for the reduced transition metal element and / or low-valent transition metal oxide to react with Na2O to generate sodium supplement material, and it is also beneficial to improve the bonding strength between the coating layer and the substrate, which is beneficial for the battery to have high first discharge gram capacity, high first coulomb efficiency and good cycle performance.

[0143] Optionally, the holding time of the sintering treatment can be 5h-8h.

[0144] By adjusting the type of aryl sodium, the concentration of the aryl sodium solution, the molar ratio of the sodium-containing layered transition metal oxide to the Na element in the aryl sodium, the parameters for the reaction of the sodium-containing layered transition metal oxide and the aryl sodium solution (such as reaction temperature, reaction time, stirring rate), the sintering treatment temperature, the sintering treatment insulation time and other parameters, the thickness of the coating layer, the weight content of the coating layer and other parameters can be adjusted.

[0145] In some embodiments, the inert gas may include one or more of argon, helium, nitrogen, and a hydrogen-argon mixture.

[0146] In some embodiments, the sodium-containing layered transition metal oxide comprises Na c N d M″ e P f O g Q h, 0.67≤c≤1.2, 0≤d≤1 / 3, 0<e≤1, 0≤f≤1 / 3, 1.9≤g≤2, 0≤h≤0.1, and the values ​​of c, d, e, f, g, and h satisfy the charge balance of the chemical formula; M″ includes one or more of Ni, Mn, Fe, Co, Cr, Cu, V, and Ti; N includes one or more metal elements in Group IA, Group IIA, and Zn; P includes one or more of a first metal element and a first non-metal element, the first metal element includes one or more metal elements in Group IA, Group IIA, Group IIIA, Group IVA, Group VA, Group IIB, Group IVB, Group VB, and Group VIB, and the first non-metal element includes one or more non-metal elements in Group IIIA, Group IVA, Group VA, and Group VIA; Q includes one or more non-metal elements in Group VA and Group VIIA.

[0147] Optionally, M″ may include two or more of Ni, Mn, Fe, Co, Cr, Cu, V, and Ti.

[0148] Optionally, N may include one or more elements of Li, Mg, Ca, and Zn.

[0149] Optionally, the first metal element may include one or more elements of Li, Zr, Sb, Nb, Mg, Ca, Mo, Zn, W, Bi, Sn, Ge, Al, Ba, and Sr.

[0150] Optionally, the first non-metal element may include one or more elements of Si, P, B, S, and Se.

[0151] Optionally, Q may include one or more elements of F, Cl, and N.

[0152] In some embodiments, the sodium-containing layered transition metal oxide may include, but is not limited to, one or more of an O3 phase, a P2 phase, and a P3 phase.

[0153] The method for preparing the positive electrode active material of the embodiment of the present application can prepare the positive electrode active material as described above in the present application. Unless otherwise specified, all raw materials used in the above preparation method can be obtained from the market.

[0154] [Positive electrode]

[0155] The embodiment of the present application also provides a positive electrode plate.

[0156] The positive electrode sheet includes a positive electrode current collector and a positive electrode film layer disposed on at least one surface of the positive electrode current collector, and the positive electrode film layer includes the positive electrode active material as described above in the present application or the positive electrode active material prepared by the preparation method as described above in the present application. Thus, the battery can have high first discharge gram capacity, high first coulomb efficiency and good cycle performance.

[0157] In some embodiments, the content of the positive electrode active material in the positive electrode film layer may be 50% to 99%, optionally 85% to 99%, based on the total weight of the positive electrode film layer.

[0158] The positive electrode current collector has two surfaces opposite to each other in the thickness direction thereof, and the positive electrode film layer is arranged on any one or both of the two opposite surfaces of the positive electrode current collector.

[0159] The positive electrode film layer may also include other positive electrode active materials known in the art, for example, including but not limited to one or more of fluoride, sulfide, phosphate, pyrophosphate, metal organic framework / metal hexanide and organic compound. These other positive electrode active materials may be used alone or in combination of two or more.

[0160] In some embodiments, the positive electrode film layer may also optionally include a positive electrode conductive agent. As an example, the positive electrode conductive agent may include, but is not limited to, one or more of superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0161] In some embodiments, the positive electrode film layer may also optionally include a positive electrode binder. As an example, the positive electrode binder may include, but is not limited to, polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, fluorinated acrylic resin, styrene-butadiene rubber (SBR), water-soluble unsaturated resin SR-1B, water-based acrylic resin (e.g., polyacrylic acid PAA, polymethacrylic acid PMAA, sodium polyacrylate PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), carboxymethyl chitosan (CMCS) One or more.

[0162] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. As an example of a metal foil, aluminum foil may be used. The composite current collector may include a polymer material base layer and a metal material layer formed on at least one surface of the polymer material base layer. As an example, the metal material may include, but is not limited to, one or more of aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver, and silver alloy. As an example, the polymer material base layer may include, but is not limited to, one or more of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), and polyethylene (PE).

[0163] The positive electrode film layer is usually formed by coating the positive electrode slurry on the positive electrode current collector, drying and cold pressing. The positive electrode slurry is usually formed by dispersing the positive electrode active material, optional conductive agent, optional binder and any other components in a solvent and stirring them uniformly. The solvent can be N-methylpyrrolidone (NMP), but is not limited thereto.

[0164] [Negative electrode]

[0165] The battery cell includes a negative electrode plate. The structure and composition of the negative electrode plate can be selected according to the type of the battery cell, and the embodiment of the present application is not limited to this.

[0166] In some embodiments, the negative electrode sheet may include a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector and including a negative electrode active material. For example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.

[0167] The negative electrode active material may be a material known in the art. For example, the negative electrode active material includes but is not limited to one or more of soft carbon, hard carbon, and mesophase micro carbon beads.

[0168] In some embodiments, the negative electrode film layer may further optionally include a negative electrode conductive agent. As an example, the negative electrode conductive agent may include, but is not limited to, one or more of superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0169] In some embodiments, the negative electrode film layer may further optionally include a negative electrode binder. As an example, the negative electrode binder may include, butadiene styrene rubber (SBR), water-soluble unsaturated resin SR-1B, water-based acrylic resin (e.g., polyacrylic acid PAA, polymethacrylic acid PMAA, sodium polyacrylate PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), carboxymethyl chitosan (CMCS) or more.

[0170] In some embodiments, the negative electrode film layer may further include other additives. As an example, the other additives may include a thickener, such as sodium carboxymethyl cellulose (CMC), a PTC thermistor material, and the like.

[0171] The negative electrode film layer is usually formed by coating the negative electrode slurry on the negative electrode current collector, drying and cold pressing. The negative electrode slurry is usually formed by dispersing the negative electrode active material, optional conductive agent, optional binder, and other optional auxiliary agents in a solvent and stirring them uniformly. The solvent can be N-methylpyrrolidone (NMP) or deionized water, but is not limited thereto.

[0172] The negative electrode plate does not exclude other additional functional layers besides the negative electrode film layer. For example, in some embodiments, the negative electrode plate may also include a conductive primer layer (e.g., composed of a conductive agent and a binder) sandwiched between the negative electrode current collector and the negative electrode film layer and disposed on the surface of the negative electrode current collector; in some embodiments, the negative electrode plate may also include a protective layer covering the surface of the negative electrode film layer.

[0173] In some embodiments, the negative electrode plate may include a negative electrode current collector and a metal layer disposed on at least one surface of the negative electrode current collector. The metal material in the metal layer may include but is not limited to one or more of sodium element and sodium alloy.

[0174] The sodium alloy may be an alloy formed by metallic sodium and other metallic elements or non-metallic elements. As an example, the other metallic elements in the sodium alloy may include, but are not limited to, one or more of tin, zinc, aluminum, magnesium, silver, gold, gallium, indium, and platinum, and the non-metallic elements in the sodium alloy may include one or more of boron, carbon, and silicon.

[0175] In some embodiments, the negative electrode plate may be a sodium plate (foil) or a sodium alloy plate (foil).

[0176] In some embodiments, the negative electrode sheet may include a negative electrode current collector to assemble into a negative electrode-free sodium metal battery cell.

[0177] In some embodiments, the negative electrode current collector may include a metal foil, a three-dimensional porous current collector, or a composite current collector. As an example of a metal foil, copper foil, copper alloy foil, nickel foil, nickel alloy foil, aluminum foil, and aluminum alloy foil may be used. As an example of a three-dimensional porous current collector, copper mesh, nickel mesh, foam copper, foam nickel, and foam aluminum may be used. The composite current collector may include a polymer material base layer and a metal material layer formed on at least one surface of the polymer material base layer. As an example, the metal material may include, but is not limited to, one or more of copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, aluminum, aluminum alloy, silver, and silver alloy. As an example, the polymer material base layer may include, but is not limited to, one or more of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), and polyethylene (PE).

[0178] [Electrolytes]

[0179] The battery cell includes an electrolyte. The present application has no specific restrictions on the type of electrolyte, which can be selected according to needs. For example, the electrolyte can include one or more selected from solid electrolytes and liquid electrolytes (ie, electrolytes).

[0180] In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.

[0181] In some embodiments, as an example, the electrolyte salt may include, but is not limited to, one or more of sodium hexafluorophosphate (NaPF6), sodium tetrafluoroborate (NaBF4), sodium perchlorate (NaClO4), sodium hexafluoroarsenate (NaAsF6), sodium bis(fluorosulfonyl)imide (NaFSI), sodium bis(trifluoromethanesulfonyl)imide (NaTFSI), sodium trifluoromethanesulfonate (NaTFS), sodium difluorooxalatoborate (NaDFOB), sodium dioxalatoborate (NaBOB), sodium difluorophosphate (NaPO2F2), sodium difluorobis(oxalatophosphate) (NaDFOP), and sodium tetrafluorooxalatophosphate (NaTFOP).

[0182] In some embodiments, the solvent may include, but is not limited to, one or more of an ester solvent, a sulfone solvent, and an ether solvent. As an example, the solvent may include, but is not limited to, one or more of ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), cyclopentane (SF), dimethyl sulfone (MSM), methyl ethyl sulfone (EMS), diethyl sulfone (ESE), ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, and tetrahydrofuran.

[0183] In some embodiments, the electrolyte may further include additives. For example, the additives may include negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high temperature performance, and additives that improve battery low temperature power performance.

[0184] [Isolation film]

[0185] Battery cells using electrolytes and some battery cells using solid electrolytes also include a separator, which is disposed between the positive electrode sheet and the negative electrode sheet and mainly serves to prevent internal short circuits.

[0186] The present application has no particular limitation on the type of isolation membrane, and any known porous isolation membrane with good chemical stability and mechanical stability can be selected.

[0187] In some embodiments, the material of the isolation membrane may include, but is not limited to, one or more of glass fiber, non-woven fabric, polyethylene, polypropylene, and polyvinylidene fluoride. The isolation membrane may be a single-layer film or a multi-layer composite film. When the isolation membrane is a multi-layer composite film, the materials of each layer are the same or different.

[0188] The preparation method of battery cells is well known. In some embodiments, the positive electrode sheet, the separator, the negative electrode sheet and the electrolyte can be assembled to form a battery cell. As an example, the positive electrode sheet, the separator, and the negative electrode sheet can be formed into an electrode assembly through a winding process and / or a lamination process, and the electrode assembly is placed in an outer package, and the above-mentioned electrolyte is injected after drying. After packaging, standing, formation and other processes, a battery cell is obtained. Multiple battery cells can also be further connected in series, in parallel or in mixed connection to form a battery module. Multiple battery modules can also be connected in series, in parallel or in mixed connection to form a battery pack. In some embodiments, multiple battery cells can also directly form a battery pack.

[0189] Electrical devices

[0190] The embodiment of the present application also provides an electrical device, which includes a battery provided in the embodiment of the present application, and the battery is used to provide electrical energy. The battery can be used as a power source for the electrical device, and can also be used as an energy storage unit for the electrical device. The electrical device can be, but is not limited to, a mobile device (such as a mobile phone, a tablet computer, a laptop computer, etc.), an electric vehicle (such as a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, an electric bicycle, an electric scooter, an electric golf cart, an electric truck, etc.), an electric train, a ship and a satellite, an energy storage system, etc.

[0191] The electrical device can select a specific type of battery, such as a battery cell, a battery module or a battery pack, according to its usage requirements.

[0192] Figure 6 Schematic diagram of an electric device as an example. The electric device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. In order to meet the requirements of the electric device for high power and high energy density, a battery pack or a battery module may be used.

[0193] As another example, the electric device may be a mobile phone, a tablet computer, a notebook computer, etc. The electric device is usually required to be light and thin, and a battery cell may be used as a power source.

[0194] Example

[0195] The following examples describe the disclosure of the present application in more detail, and these examples are only for illustrative purposes, as it is obvious to those skilled in the art that various modifications and variations can be made within the scope of the disclosure of the present application. Unless otherwise stated, all parts, percentages and ratios reported in the following examples are based on mass, and all reagents used in the examples are commercially available or synthesized according to conventional methods and can be used directly without further treatment, and the instruments used in the examples are commercially available.

[0196] Example 1

[0197] (1) Preparation of positive electrode active materials

[0198] The nickel-manganese precursor was prepared by hydroxide coprecipitation method, and then sintered with sodium nitrate at high temperature to obtain the target product Na 1.05 Ni 0.55 Mn 0.45 O2. Na 1.05 Ni 0.55 Mn 0.45 O2 was added to a 1.5 mol / L tetrahydrofuran solution of sodium naphthalene, and the reaction was stirred for 8 hours at a reaction temperature of 25°C and a stirring speed of 500 r / min. Afterwards, the powder was washed with ethanol 2-3 times, and then the obtained powder was placed in a box furnace, nitrogen was introduced, and sintered at 750°C for 5 hours to obtain the positive electrode active material. 1.05 Ni 0.55 Mn 0.45 The molar ratio of O2 to the Na element in sodium naphthalene is 1:0.1.

[0199] (2) Preparation of positive electrode sheet

[0200] The positive electrode active material is mixed with acetylene black and PVDF in a weight ratio of 95:3:2, and then a proper amount of NMP is added and stirred to form a uniform positive electrode slurry; the positive electrode slurry is coated on the positive electrode current collector aluminum foil, and the positive electrode sheet is obtained by drying and cold pressing.

[0201] (3) Preparation of negative electrode sheet

[0202] Hard carbon, acetylene black, styrene-butadiene rubber and sodium carboxymethyl cellulose are mixed in a weight ratio of 95:2:2:1, and then an appropriate amount of deionized water is added and stirred to form a uniform negative electrode slurry; the negative electrode slurry is coated on the negative electrode current collector copper foil, dried and cold pressed to obtain a negative electrode sheet.

[0203] (4) Preparation of electrolyte

[0204] In an argon-filled glove box with a water content of <1 ppm, diethylene glycol dimethyl ether and tetrahydrofuran were mixed in a weight ratio of 1:3, and NaPF6 with a concentration of 1.0 mol / L was added. After stirring evenly, an electrolyte was obtained.

[0205] (5) Preparation of batteries

[0206] The positive electrode sheet, the isolation film (polypropylene film with a thickness of 12 μm), and the negative electrode sheet are stacked in order, so that the isolation film is placed between the positive electrode sheet and the negative electrode sheet to play an isolating role, and then wound to obtain an electrode assembly; the electrode assembly is placed in an outer package, and the prepared electrolyte is injected into the dried battery, and then the battery is obtained after vacuum packaging, standing, forming, shaping and other processes.

[0207] Examples 2 to 6

[0208] Except that the type of aryl sodium or the type of aprotic solvent in the aryl sodium solution in the preparation of the positive electrode active material in step (1) is different, the preparation process of the battery is the same as that of Example 1. Specific parameters are shown in Table 1.

[0209] Examples 7 to 11

[0210] Except for the different sintering temperature in the preparation of the positive electrode active material in step (1), the preparation process of the battery is the same as that of Example 1. Specific parameters are shown in Table 1.

[0211] Examples 12 to 15

[0212] Except that the concentration of the sodium aryl solution in the preparation of the positive electrode active material in step (1) is different, the preparation process of the battery is the same as that of Example 1. Specific parameters are shown in Table 1.

[0213] Examples 16 to 19

[0214] Except that the molar ratio of the sodium-containing layered transition metal oxide to the Na element in the sodium aryl group in the preparation of the positive electrode active material in step (1) is different, the preparation process of the battery is the same as that of Example 1. Specific parameters are shown in Table 1.

[0215] Examples 20 to 23

[0216] Except for the different reaction temperature of the sodium-containing layered transition metal oxide and the aryl sodium solution in the preparation of the positive electrode active material in step (1), the preparation process of the battery is the same as that of Example 1. Specific parameters are shown in Table 1.

[0217] Examples 24 to 27

[0218] Except that the type of sodium-containing layered transition metal oxide in the preparation of the positive electrode active material in step (1) is different, the preparation process of the battery is the same as that of Example 1. Specific parameters are shown in Table 1.

[0219] Comparative Example 1

[0220] Except for Na 1.05 Ni 0.55 Mn 0.45 Except that O2 is used as the positive electrode active material, the preparation process of the battery is the same as that of Example 1.

[0221] Comparative Example 2

[0222] The preparation process of the battery is the same as that of Example 1 except that the preparation process of the positive electrode active material in step (1) is different.

[0223] The nickel-manganese precursor was prepared by hydroxide coprecipitation method, and then sintered with sodium nitrate at high temperature to obtain the target product Na 1.05 Ni 0.55 Mn 0.45 O2. Na 1.05 Ni 0.55 Mn 0.45 O2 was added to a 1.5 mol / L tetrahydrofuran solution of sodium naphthalene, and the reaction was stirred for 8 hours at a reaction temperature of 25°C and a stirring speed of 500 r / min; then washed with ethanol 2-3 times to obtain a positive electrode active material. 1.05 Ni 0.55 Mn 0.45 The molar ratio of O2 to the Na element in sodium naphthalene is 1:0.1.

[0224] Comparative Example 3

[0225] Except for the different preparation process of the positive electrode plate in step (2), the preparation process of the battery is the same as that of Example 1.

[0226] The nickel-manganese precursor was prepared by hydroxide coprecipitation method, and then sintered with sodium nitrate at high temperature to obtain the target product Na 1.05 Ni 0.55 Mn 0.45 O2. The target product Na 1.05 Ni 0.55 Mn 0.45 O2, Na2NiO2, acetylene black and PVDF are mixed in a weight ratio of 85:10:3:2, and then an appropriate amount of NMP is added and stirred to form a uniform positive electrode slurry; the positive electrode slurry is coated on the positive electrode current collector aluminum foil, and the positive electrode sheet is obtained by drying and cold pressing.

[0227] Comparative Example 4

[0228] Except for the different preparation process of the positive electrode plate in step (2), the preparation process of the battery is the same as that of Example 1.

[0229] The nickel-manganese precursor was prepared by hydroxide coprecipitation method, and then sintered with sodium nitrate at high temperature to obtain the target product Na 1.05 Ni 0.55 Mn 0.45 O2. The target product Na 1.05 Ni 0.55 Mn 0.45 O2, Na2CO3, acetylene black and PVDF are mixed in a weight ratio of 85:10:3:2, and then an appropriate amount of NMP is added and stirred to form a uniform positive electrode slurry; the positive electrode slurry is coated on the positive electrode current collector aluminum foil, and the positive electrode sheet is obtained by drying and cold pressing.

[0230] Test Section

[0231] (1) Battery capacity test

[0232] At 25°C, the prepared battery is first charged to 4.2V at a constant current of 1C, further charged at a constant voltage to a current of 0.05C, and then discharged to 2.5V at a constant current of 1C. This is a charge and discharge cycle process, and the discharge capacity this time is taken as the battery capacity.

[0233] (2) Battery cycle performance test

[0234] At 25°C, the prepared battery is first charged to 4.2V at a constant current of 1C, further charged to a current of 0.05C at a constant voltage, and then discharged to 2.5V at a constant current of 1C. This is a charge and discharge cycle process, and the discharge capacity this time is the discharge capacity of the first cycle. The battery is subjected to a cyclic charge and discharge test in the above manner. When the discharge capacity of the battery decays to 80% of the discharge capacity of the first cycle, the test is stopped and the number of cycles of the battery is recorded.

[0235] (3) First discharge capacity and coulomb efficiency test of button cell

[0236] The positive electrode sheet prepared above (the positive electrode film layer on one surface of the aluminum foil needs to be wiped off), the isolation membrane, and the sodium metal sheet are cut into discs of appropriate sizes and stacked in order, so that the isolation membrane is placed between the positive electrode sheet and the sodium metal sheet to play an isolation role. The isolation membrane is soaked with the electrolyte prepared above, and then compacted to obtain a button battery.

[0237] At 25°C, the button cell was charged to 4.2V at a constant current of 0.1C to obtain the first charge capacity of the button cell; then discharged to 2.6V at a constant current of 0.1C to obtain the first discharge capacity of the button cell. The first discharge capacity (mAh / g) of the positive electrode active material = the first discharge capacity of the button cell / the mass of the positive electrode active material. The first coulombic efficiency of the positive electrode active material = the first discharge capacity of the button cell / the first charge capacity of the button cell.

[0238] The test results are shown in Table 2.

[0239] Table 1

[0240]

[0241] Table 2

[0242]

[0243] It can be seen from the test results of Examples 1 to 27 and Comparative Examples 1 to 4 that the positive electrode active material provided in the embodiments of the present application can enable the sodium battery to have high first discharge gram capacity, high first coulombic efficiency and good cycle performance.

[0244] The coating layer of the positive electrode active material includes a sodium supplement material. When the battery is charged for the first time, the active sodium in the sodium supplement material can make up for the loss of active sodium caused by the formation of the SEI film at the negative electrode, thereby improving the battery's first discharge gram capacity and first coulomb efficiency. The coating layer also satisfies the trend that the concentration of the Na element decreases from the surface of the coating layer away from the substrate to the surface of the coating layer close to the substrate, which is conducive to promoting the release of active sodium, thereby facilitating the battery to have a higher first discharge gram capacity and a higher first coulomb efficiency. The positive electrode active material has a low risk of decomposition and gas production during the battery's charge and discharge process, thereby enabling the positive electrode film layer to have good adhesion to the positive electrode current collector, reducing the positive electrode contact resistance, and thus enabling the battery to have good cycle performance.

[0245] The coating layer is in-situ generated on at least a portion of the surface of the substrate, so that the bonding strength between the coating layer and the substrate is relatively high. After the active sodium in the sodium supplement material is removed, the remaining material (i.e., the remaining product after the sodium supplement material is de-sodiumized) can also allow the coating layer to isolate the electrolyte from direct contact with the substrate, thereby reducing battery side reactions and reducing the probability of transition metal ions in the remaining material (i.e., the remaining product after the sodium supplement material is de-sodiumized) being dissolved into the electrolyte, thereby enabling the battery to have better cycle performance.

[0246] The coating layer of the positive electrode active material provided in the embodiment of the present application is obtained by mixing and reacting a sodium-containing layered transition metal oxide with an aryl sodium solution, and then sintering. In the above embodiments, the sodium-containing layered transition metal oxide matrix is ​​a multi-element material, which also makes the sodium-supplementing material in the coating layer generated in situ on the surface of the matrix usually multi-phase. In Table 2, only some of the main sodium-supplementing material components of the coating layer are shown, and of course the coating layer may also contain other components. And the average valence of the transition metal element M' in the matrix of the positive electrode active material provided in the embodiment of the present application is also greater than the average valence of the transition metal element M in the coating layer. The average valence of the transition metal element in the coating layer is low, so the coating layer has higher stability and lower risk of decomposition and gas production, which can further improve the adhesion between the positive electrode film layer and the positive electrode current collector, reduce the positive electrode contact resistance, and further improve the cycle performance of the battery.

[0247] Comparative Example 1 uses a positive electrode active material without sodium supplementation to prepare a battery. From the test results in Table 2, it can be seen that the battery has low first coulombic efficiency, low discharge capacity and poor cycle performance.

[0248] The positive electrode active material prepared in Comparative Example 2 was not sintered, so after reduction with sodium naphthalene, Na2O was generated on the surface of the positive electrode active material, and Na2O absorbed moisture from the environment to generate residual alkali such as Na2CO3, thereby affecting the performance of the battery. From the test results in Table 2, it can be seen that the battery has low initial coulombic efficiency, low discharge capacity and poor cycle performance.

[0249] Comparative Example 3 adds the sodium supplement additive Na2NiO2 directly to the positive electrode slurry, which can improve the first coulombic efficiency and the first discharge gram capacity of the battery, but the battery cycle performance is still poor. This is because after the active sodium in the sodium supplement additive Na2NiO2 is released, a relatively high mass proportion of by-products will be left in the positive electrode film layer, and the transition metal ions in the by-products are easily dissolved into the electrolyte, and then these transition metal ions will be reduced and deposited on the negative electrode, thereby destroying the structure of the SEI film, reducing the discharge capacity of the battery and affecting the release and embedding of sodium ions, which leads to poor battery cycle performance.

[0250] Comparative Example 4: The sodium supplement additive Na2CO3 is directly added to the positive electrode slurry. Na2CO3 is easily decomposed to produce gas, which will leave more holes in the positive electrode film layer, thereby reducing the adhesion between the positive electrode film layer and the positive electrode current collector, and increasing the positive electrode contact resistance. From the test results in Table 2, it can be seen that the battery has low initial coulomb efficiency, low discharge capacity and poor cycle performance.

[0251] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.

Claims

1. A positive electrode active material, characterized in that: The positive electrode active material includes a substrate and a coating layer formed on at least a portion of the surface of the substrate; The matrix includes a layered transition metal oxide containing sodium; The coating layer includes a sodium supplement material, and the coating layer includes Na element, M element and O element, where M represents a transition metal; And the coating layer satisfies: the concentration of the Na element tends to decrease from the surface of the coating layer far from the substrate to the surface of the coating layer close to the substrate.

2. The positive electrode active material according to claim 1, characterized in that The sodium-containing layered transition metal oxide includes an M' element, where M' represents a transition metal, and an average valence of the M' element in the sodium-containing layered transition metal oxide is greater than an average valence of the M element in the coating layer.

3. The positive electrode active material according to claim 1 or 2, characterized in that: The coating layer satisfies: the average valence of the M element increases from the surface of the coating layer far from the substrate to the surface of the coating layer close to the substrate.

4. The positive electrode active material according to claim 2, characterized in that In the coating layer, M includes one or more of Ni, Mn, Fe, Co, Cr, Cu, V, and Ti, and may optionally include two or more of Ni, Mn, Fe, Co, Cr, Cu, V, and Ti; and / or, In the sodium-containing layered transition metal oxide, M′ includes one or more of Ni, Mn, Fe, Co, Cr, Cu, V, and Ti, and may optionally include two or more of Ni, Mn, Fe, Co, Cr, Cu, V, and Ti.

5. The positive electrode active material according to any one of claims 1 to 4, characterized in that: The coating layer is in-situ generated on at least a portion of the surface of the substrate.

6. The positive electrode active material according to any one of claims 1 to 5, characterized in that: The thickness H of the coating layer and the average diameter D of the positive electrode active material satisfy: 0<H / D≤0.15, optionally, 0.02≤H / D≤0.

11.

7. The positive electrode active material according to any one of claims 1 to 6, characterized in that: The weight content of the coating layer in the positive electrode active material is 2%-40%, optionally 5%-20%, based on the total weight of the positive electrode active material.

8. The positive electrode active material according to any one of claims 1 to 7, characterized in that: The volume distribution particle size Dv50 of the positive electrode active material is 1 μm-10 μm, and can be optionally 3 μm-8 μm.

9. The positive electrode active material according to any one of claims 1 to 8, characterized in that: In the coating layer, the chemical molar ratio of the Na element, the M element and the O element is (1-6):(1-2):(2-4). Optionally, the chemical molar ratio of the Na element, the M element and the O element is (1-6):1:(2-4).

10. The positive electrode active material according to any one of claims 1 to 9, characterized in that: The coating layer includes one or more of NaMO2, Na2MO2, Na2MO3, Na3MO2, Na3MO3, Na4MO3, Na5MO3, Na5MO4, and Na6MO4, and may be selected to include two or more of NaMO2, Na2MO2, Na2MO3, Na3MO2, Na3MO3, Na4MO3, Na5MO3, Na5MO4, and Na6MO4; Optionally, M independently includes any one of Ni, Mn, Fe, Co, Cr, Cu, V, and Ti.

11. The positive electrode active material according to any one of claims 1 to 10, characterized in that: The sodium-containing layered transition metal oxide includes Na c N d M″ e P f O g Q h , 0.67≤c≤1.2, 0≤d≤1 / 3, 0<e≤1, 0≤f≤1 / 3, 1.9≤g≤2, 0≤h≤0.1, and the values ​​of c, d, e, f, g, and h satisfy the charge balance of the chemical formula; M″ includes one or more of Ni, Mn, Fe, Co, Cr, Cu, V, and Ti, and can be selected to include two or more of Ni, Mn, Fe, Co, Cr, Cu, V, and Ti; N includes one or more metal elements of Group IA, Group IIA, and Zn, and can be selected to include one or more of Li, Mg, Ca, and Zn; P includes one or more of a first metal element and a first non-metal element, and the first metal element It includes one or more metal elements of Group IA, Group IIA, Group IIIA, Group IVA, Group VA, Group IIB, Group IVB, Group VB, and Group VIB, and may be selected from one or more elements of Li, Zr, Sb, Nb, Mg, Ca, Mo, Zn, W, Bi, Sn, Ge, Al, Ba, and Sr; the first non-metallic element includes one or more non-metallic elements of Group IIIA, Group IVA, Group VA, and Group VIA, and may be selected from one or more elements of Si, P, B, S, and Se; Q includes one or more non-metallic elements of Group VA and Group VIIA, and may be selected from one or more elements of F, Cl, and N; Optionally, the sodium-containing layered transition metal oxide includes one or more of an O3 phase, a P2 phase, and a P3 phase.

12. The positive electrode active material according to any one of claims 1 to 11, characterized in that: The weight content of the sodium supplement material in the coating layer is more than 97%, and can be optionally 97%-99%, based on the total weight of the coating layer.

13. The positive electrode active material according to claim 12, characterized in that: The coating layer also includes one or more of sodium oxide, sodium hydroxide and sodium carbonate.

14. The positive electrode active material according to any one of claims 12 to 13, characterized in that: The sodium-containing layered transition metal oxide includes an M' element and a non-valent metal element, where M' represents a transition metal, and the coating layer further includes one or more of an oxide of the non-valent metal element and a salt of the non-valent metal element.

15. A method for preparing a positive electrode active material, characterized in that: The steps include: providing a sodium-containing layered transition metal oxide and a sodium aryl solution; The sodium-containing layered transition metal oxide is mixed with the sodium aryl solution to react, and after the reaction is completed, the powder is washed and dried to obtain a powder; The obtained powder is sintered in an inert gas atmosphere to obtain a positive electrode active material. The positive electrode active material comprises a substrate and a coating formed on at least a portion of the surface of the substrate; the substrate comprises a layered transition metal oxide containing sodium; the coating comprises a sodium supplement material, the coating comprises Na element, M element and O element, M represents a transition metal; and the coating satisfies: the concentration of the Na element tends to decrease from the surface of the coating far from the substrate to the surface of the coating close to the substrate.

16. The preparation method according to claim 15, characterized in that: In the step of mixing the sodium-containing layered transition metal oxide with the sodium aryl solution for reaction, the molar ratio of the sodium-containing layered transition metal oxide to the Na element in the sodium aryl is 1:(0.01-0.2), and can be optionally 1:(0.05-0.1).

17. The preparation method according to any one of claims 15-16, characterized in that: In the step of mixing the sodium-containing layered transition metal oxide with the sodium aryl solution for reaction, The reaction temperature is 15°C-60°C, optionally 25°C-45°C; and / or, The reaction time is 5h-20h, and can be optionally 8h-16h.

18. The preparation method according to any one of claims 15 to 17, characterized in that: In the step of mixing the sodium-containing layered transition metal oxide with the sodium aryl solution for reaction, the reaction is carried out under stirring conditions; optionally, the stirring speed is 100r / min-1000r / min, and more optionally 200r / min-700r / min.

19. The preparation method according to any one of claims 15 to 18, characterized in that: In the step of sintering the obtained powder in an inert gas atmosphere, The sintering temperature is 500°C-950°C, and can be 600°C-900°C; and / or, The holding time of the sintering treatment is 3h-9h, and can be 5h-8h; and / or, The inert gas includes one or more of argon, helium, nitrogen, and a hydrogen-argon mixed gas.

20. The preparation method according to any one of claims 15 to 19, characterized in that: The concentration of the aryl sodium solution is 0.5 mol / L-3.5 mol / L, and can be 1 mol / L-2 mol / L; and / or, The aryl sodium includes one or more of sodium naphthalene, sodium biphenyl, sodium phenyl, sodium phenanthrene, sodium anthracene, sodium pyrene, sodium bipyridine, and sodium tetracene; and / or, The solvent of the sodium aryl solution includes an aprotic solvent. Optionally, the aprotic solvent includes one or more of ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, tetrahydrofuran, N,N-dimethylformamide, diethyl ether, diisopropyl ether, diethylene glycol dimethyl ether, methyl tert-butyl ether, ethyl ether, acetonitrile, and dimethyl sulfoxide.

21. The preparation method according to any one of claims 15 to 20, characterized in that: The sodium-containing layered transition metal oxide includes Na c N d M″ e P f O g Q h , 0.67≤c≤1.2, 0≤d≤1 / 3, 0<e≤1, 0≤f≤1 / 3, 1.9≤g≤2, 0≤h≤0.1, and the values ​​of c, d, e, f, g, and h satisfy the charge balance of the chemical formula; M″ includes one or more of Ni, Mn, Fe, Co, Cr, Cu, V, and Ti, and can be selected to include two or more of Ni, Mn, Fe, Co, Cr, Cu, V, and Ti; N includes one or more metal elements of Group IA, Group IIA, and Zn, and can be selected to include one or more of Li, Mg, Ca, and Zn; P includes one or more of a first metal element and a first non-metal element, and the first metal element It includes one or more metal elements of Group IA, Group IIA, Group IIIA, Group IVA, Group VA, Group IIB, Group IVB, Group VB, and Group VIB, and may be selected from one or more elements of Li, Zr, Sb, Nb, Mg, Ca, Mo, Zn, W, Bi, Sn, Ge, Al, Ba, and Sr; the first non-metallic element includes one or more non-metallic elements of Group IIIA, Group IVA, Group VA, and Group VIA, and may be selected from one or more elements of Si, P, B, S, and Se; Q includes one or more non-metallic elements of Group VA and Group VIIA, and may be selected from one or more elements of F, Cl, and N; Optionally, the sodium-containing layered transition metal oxide includes one or more of an O3 phase, a P2 phase, and a P3 phase.

22. A positive electrode sheet, comprising a positive electrode current collector and a positive electrode film layer disposed on at least one surface of the positive electrode current collector, characterized in that: The positive electrode film layer comprises the positive electrode active material according to any one of claims 1 to 14 or the positive electrode active material prepared by the preparation method according to any one of claims 15 to 21, Optionally, the weight content of the positive electrode active material in the positive electrode film layer is 50%-99%, more preferably 80%-99%, based on the total weight of the positive electrode film layer.

23. A battery, characterized in that: Including the positive electrode sheet as described in claim 22.

24. An electrical device, characterized in that: The battery according to claim 23 is used to provide electrical energy.

Citation Information

Patent Citations

  • Sodium ion gradient doped spinel structure positive electrode active material and preparation method thereof

    CN111029560A

  • Preparation method of sodium ion battery positive electrode material

    CN115385380A

  • Sodium ion positive electrode material, preparation method and application thereof, sodium ion battery, sodium ion battery pack and equipment

    CN116190657A

  • Anion-cation co-doped and coated sodium ion battery positive electrode material and preparation method thereof

    CN116417590A

  • Nickel-iron-manganese ternary layered positive electrode material and preparation method thereof

    CN116454251A